Islamic Financial Technology Dalam Penerapan Di Lembaga Keuangan Syariah - Yanti Sirait, Frida; Fitri, Mulyana; Marliyah, Marliyah (Al-Sharf: Jurnal Ekonomi Islam, 2023)
The research objective is to analyze the Islamic financial system (Islamic Financial Technology) which plays a role in Sharia Financial Institutions. The method used in this research is descriptive qualitative or library research sourced from reputable books and journals. Research results show that Islamic financial technology plays an active role in Sharia Financial Institutions. So that the development of sharia fintech in Indonesia can run and minimize the spread of illegal activities related to fintech, it is necessary to implement regulations that are easier to understand, stronger infrastructure, and socialize about sharia banking.